Acute effects of body-weight resistance exercises on blood pressure and glycemia in middle-aged adults with hypertension. (2nd January 2021) - Ferrari, Rodrigo; Cadore, Eduardo Lusa; Périco, Bibiana; Kothe, Gabriela Bartholomay
ABSTRACT: Objective: The purpose of the present study was to evaluate the acute effects of single session of body-weight resistance exercises on blood pressure (BP) and glycemia in middle-aged adults with hypertension. Methods: Twenty-three participants took part in this trial with crossover design and performed two experimental sessions in a random order: Body-weight resistance exercise session (BWR) and a control session without exercise. BWR was composed of four exercises: inverted row, squat, , and sit-ups. The participants performed 3 sets of 30 s, in which they were instructed to perform as much repetitions as possible and as fast as possible. After each session, BP and glycemia were measured continuously for 60 min. Results: Systolic BP decreased after BWR when compared with control at post 45ʹ: −7 (95%CI:-11 to −2) mmHg, p = .003 and post60ʹ: −7 (95%CI:-12 to −3) mmHg, p = .003. Diastolic BP decreased after BWR when compared with control at post 15ʹ: −6 (95%CI:-9 to −3) mmHg, p < .001; post 30ʹ: −6 (95%CI:-9 to −2) mmHg, p = .001; post45ʹ: −5 (95%CI:-9 to −2) mmHg, p = .005; and post60ʹ: −6 (95%CI: −8 to −3) mmHg, p < .001. No significant difference was found in glycemia between BWR and control sessions. Conclusion: BWR acutely reduces BP in middle-aged adults with hypertension without effects on usual glycemia responses. This alternative form of resistance training could facilitate access, adherence, and reduce health costs related to exercise programs.